Proposed primary endpoints for use in clinical trials that compare treatment options for bloodstream infection in adults: a consensus definition. (August 2017) - Harris, P.N.A.; McNamara, J.F.; Lye, D.C.; Davis, J.S.; Bernard, L.; Cheng, A.C.; Doi, Y.; Fowler, V.G.; Kaye, K.S.; Leibovici, L.; Lipman, J.; Llewelyn, M.J.; et al.
Abstract: Objectives: To define standardized endpoints to aid the design of trials that compare antibiotic therapies for bloodstream infections (BSI). Methods: Prospective studies, randomized trials or registered protocols comparing antibiotic therapies for BSI, published from 2005 to 2016, were reviewed. Consensus endpoints for BSI studies were defined using a modified Delphi process. Results: Different primary and secondary endpoints were defined for pilot (small-scale studies designed to evaluate protocol design, feasibility and implementation) and definitive trials (larger-scale studies designed to test hypotheses and influence clinical practice), as well as for Staphylococcus aureus and Gram-negative BSI. For pilot studies of S. aureus BSI, a primary outcome of success at day 7 was defined by: survival, resolution of fever, stable/improved Sequential Organ Failure Assessment (SOFA) score and clearance of blood cultures, with no microbiologically confirmed failure up to 90 days. For definitive S. aureus BSI studies, a primary outcome of success at 90 days was defined by survival and no microbiologically confirmed failure. For pilot studies of Gram-negative BSI, a primary outcome of success at day 7 was defined by: survival, resolution of fever and symptoms related to BSI source, stable or improved SOFA score and negative blood cultures. For definitive Gram-negative BSI studies, a primary outcome of survival at 90 days supported by a secondary outcome of success at day 7 (as previously defined) was agreed. Conclusions: These endpoints provide a framework to aid future trial design. Further work will be required to validate these endpoints with respect to patient-centred clinical outcomes.